Technology Acceptance Model (TAM) for Evaluating Acceptance Pega Application at PT. Sinar Mas Insurance Policy Services Division - Dessilomba, Geofiton Ardelan; Tanaamah, Andeka Rocky (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2021)
This study describes and predicts how users accept the implemented technology. This research uses a qualitative method approach. Data collection was carried out by interviewing three employees of the Policy Services Division of PT Asuransi Sinar Mas. Researchers researched in March 2020. The data obtained were then processed through data reduction, data presentation, and description conclusions. The results showed that employees in the company could accept technology because they perceive ease of use and usability. The emergence of a positive attitude towards the use of technology impacts the high interest in technology use behavior to increase the actual use of technology. The positive attitude of users towards technology is indicated by the satisfaction of using technology from employees. Researchers can measure technology acceptance based on perceived ease of use, perceived usefulness, attitudes of using technology, interest in behavior using technology, and actual behavior using technology. It is necessary to improve the actual conduct of employees using technology that can improve company performance.